The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1093/ckj/sfw021
|View full text |Cite
|
Sign up to set email alerts
|

Sevelamer carbonate reduces the risk of hypomagnesemia in hemodialysis-requiring end-stage renal disease patients

Abstract: BackgroundSevelamer has been associated with less progression of vascular calcifications. This effect could be due to a reduction in serum phosphate levels but also to other additive effects. Magnesium has been also shown to prevent vascular calcification but the effect of sevelamer on serum magnesium levels has not been thoroughly evaluated. Our aim was to analyze whether the use of sevelamer reduces the risk of hypomagnesemia in hemodialysis (HD)-requiring end-stage renal disease patients.MethodsAll prevalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…[85]. In addition, two cross-sectional studies showed an independent relationship between sevelamer and higher serum Mg levels [36,86]. It seems plausible to speculate that this effect of sevelamer depends on its adsorptive action on some substances other than P. Free fatty acids in the intestinal lumen may combine with Mg to form non-absorbable soaps.…”
Section: Mg-containing Laxativesmentioning
confidence: 99%
“…[85]. In addition, two cross-sectional studies showed an independent relationship between sevelamer and higher serum Mg levels [36,86]. It seems plausible to speculate that this effect of sevelamer depends on its adsorptive action on some substances other than P. Free fatty acids in the intestinal lumen may combine with Mg to form non-absorbable soaps.…”
Section: Mg-containing Laxativesmentioning
confidence: 99%
“…Their study showed the protective properties of sevelamer against hypomagnesemia, even considering the effects of PPI, although their findings questioned the effectiveness of sevelamer in the prevention of calcification. [ 4 ]…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that hypomagnesemia can be one of the causes of CKD and lead to increased cardiovascular mortality in patients with ESRD (requiring dialysis). [ 4 ]…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations